Mushroom Speleothems: Stromatolites That Formed in the Absence of Phototrophs - Bontognali, Tomaso R. R.; D'Angeli, Ilenia M.; Tisato, Nicola; Vasconcelos, Crisogono; Bernasconi, Stefano M.; Gonzales, Esteban R. G.; De Waele, Jo (Frontiers in Earth Science, 2016)
Unusual speleothems resembling giant mushrooms occur in Santa Catalina Cave, Cuba. Although these mineral buildups are considered a natural heritage, their composition and formation mechanism remain poorly understood. Here we characterize their morphology and mineralogy and present a model for their genesis. We propose that the mushrooms, which are mainly comprised of calcite and aragonite, formed during four different phases within an evolving cave environment. The stipe of the mushroom is an assemblage of three well-known speleothems: a stalagmite surrounded by calcite rafts that were subsequently encrusted by cave clouds (mammilaries). More peculiar is the cap of the mushroom, which is morphologically similar to cerebroid stromatolites and thrombolites of microbial origin occurring in marine environments. Scanning electron microscopy investigations of this last unit revealed the presence of fossilized extracellular polymeric substances (EPS) – the constituents of biofilms and microbial mats. These organic microstructures are mineralized with Ca-carbonate, suggesting that the mushroom cap formed through a microbially-influenced mineralization process. The existence of cerebroid Ca-carbonate buildups forming in dark caves (i.e., in the absence of phototrophs) has interesting implications for the study of fossil microbialites preserved in ancient rocks, which are today considered as one of the earliest evidence for life on Earth.